The Primacy of the City of Medina in View of the Hadith: Study of Takhrij and Syarah Hadith - Wijaya, Evan Raif Rajendriya; Haidar, Muhammad (Journal of Takhrij Al-Hadith, 2023)
The purpose of this study is to discuss the virtues of the city of Medina from a hadith perspective. This study uses an approach qualitatively by applying descriptive-analytical method. The formal object research is the science of takhrij hadith, while the object the material is the hadith of Bukhari No. 1746. Results and Discussion this research shows that the quality of hadith status is authentic who meet the qualifications of maqbul ma'mul bih for practice Islam. This study concludes that the hadith narrated by Bukhari No. 1746 relevant is used as a basis for knowing the priority of the city of Medina for inspiring generational development Muslims in the homeland.